The Rebuilding of the Kaʻba During the Period of Sulṭān Murād IV in the Context of the ʻUlamāʼ-Umarāʼ Discussions - Abdullah Çakmak (Religions)
The last stop on the Muslim pilgrimage is the Kaʻba. Like all other holy and religious places, the Kaʻba has survived due to the repairs it has undergone since its construction. However, the Kaʻba has been rebuilt at times when it was destroyed for various reasons. Since the interruption of the pilgrimage would undermine the legitimacy of the caliph, Muslims attached great importance to rebuilding the Kaʻba in such cases. The Kaʻba was last rebuilt by the Ottoman Sulṭān Murād IV after the flood of 1039/1630. However, the rebuilding process has not been without its controversies. Although the Ottoman Empire attempted to rebuild the Kaʻba out of necessity, some scholars objected to this initiative. Ibn ʻAllān, one of the leading Shafiʻi muftis of Mecca, followed the rebuilding work day by day and did not hesitate to intervene when necessary. Riḍwān Agha, who carried out the rebuilding of the Kaʻba, was able to overcome Ibn ʻAllān’s objections with fatwas from the muftis of the four sects (four Sunni schools of law) and thus completed the building work. After the Kaʻba was rebuilt, Turkish works on its history began to be produced. In this way, the public was informed that the Kaʻba could be rebuilt if necessary, and attempts were made to anticipate and prevent any potential reactions. This study aims to contribute to the history of the Kaʻba by analysing its rebuilding after the flood of 1039/1630 through debates between scholars (ʻulamāʼ) and administrators (umarāʼ) during this period. Access to the details of this issue from the works of the ʻulamāʼ who witnessed the rebuilding makes this paper unique.